If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1) + -1(x + -2) = 2x + -3 Reorder the terms: (-1 + x) + -1(x + -2) = 2x + -3 Remove parenthesis around (-1 + x) -1 + x + -1(x + -2) = 2x + -3 Reorder the terms: -1 + x + -1(-2 + x) = 2x + -3 -1 + x + (-2 * -1 + x * -1) = 2x + -3 -1 + x + (2 + -1x) = 2x + -3 Reorder the terms: -1 + 2 + x + -1x = 2x + -3 Combine like terms: -1 + 2 = 1 1 + x + -1x = 2x + -3 Combine like terms: x + -1x = 0 1 + 0 = 2x + -3 1 = 2x + -3 Reorder the terms: 1 = -3 + 2x Solving 1 = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + -2x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + -2x = -3 + 0 1 + -2x = -3 Add '-1' to each side of the equation. 1 + -1 + -2x = -3 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = -3 + -1 -2x = -3 + -1 Combine like terms: -3 + -1 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| W-2w+9=16 | | 2y+3=3(y+-7) | | -2(2m-1)+4m=2m+3 | | 39=2g-7 | | 14=15-X | | 2n-43=21 | | 2(3x-1)+5=13-(x-4) | | 71q-28q=86 | | x^2+12x+30=0 | | (3x+10)+(2x-5)=55 | | 8-3*x=20 | | 6.4-.02(x-.6)=.7x | | -28x^2-32x=0 | | 5t-2t-t=20 | | 2x-(x+5)=3(x-1) | | -2(8b+2)=4(b-6) | | -12c+16c-7c-4=-19 | | -.666(x)-5=7 | | 5a-(3a-7)=5a-3a-7 | | (x-3)(x+4)=-6 | | 4(5y-8)-3y= | | 3(x+3)=4(1+x) | | 2(x+3)=3x-1 | | -1-6m= | | 15m=50m+40000 | | 2a-5=13 | | 4-(3-x)=2 | | 6=-1(7-c) | | k/21=15 | | 7y+2(y-3)=6(y+1)-4 | | 3.8-4.9x+0.1x=2.4y+0.2 | | -17+x=-9 |